Tranformasi Panggilan Misi SurgaBerdasarkan Injil Matius 9:35 - Selan, Ongkilion (STT Pelita Dunia, 2024)
Abstract: The Transformation Call to Heaven Mission is the church's sending of believers to preach the Gospel in the world, to those who do not yet believe. Mission implementation can be realized well, so a strategy is needed to achieve the goal of reaching ethnic groups to the Gospel. This research uses a qualitative descriptive analysis method of the Gospel of Matthew 9:35. Jesus' Tri-Mission Strategy: Evangelizing, Teaching, Healing. The results of this research found a mission strategy that was divided into three steps. Compassion is the basic strategy for preaching the Gospel, moving to all places, and preaching the Gospel and teaching. This finding encourages every Christian to be more active in the Call to Heaven's Mission.